Synthesis and biological investigation of (+)-3-hydroxymethylartemisinin - Smeilus, Toni; Mousavizadeh, Farnoush; Krieger, Johannes; Tu, Xingzhao; Kaiser, Marcel; Giannis, Athanassios (Beilstein Journal of Organic Chemistry, 2019)
Herein, we describe a biomimetic entry to (+)-3-hydroxymethylartemisinin (2) as well as to the artemisinin derivatives (+)-3-hydroxymethyl-9-desmethylartemisinin (16) and (+)-3-hydroxymethyl-9-epi-artemisinin (18), starting from the known and readily available chiral aldehyde 3 and alkyne 4. Subsequently, the synthesized compounds have been evaluated for their antimalarial activity against the drug-sensitive P. falciparum NF54 strain. All of them were inactive. In addition, they did not show any toxicity against L6 cells (a primary cell line derived from rat skeletal myoblasts). These results contribute to a better understanding of artemisinins mechanism of action.
Keywords: artemisinin; biomimetic synthesis; Diels–Alder reaction; malaria; peroxides